Improvement of cycling stability of Li1.2Mn0.54Co0.13Ni0.13O2 microrods cathode material modified with in situ polymerization of aniline in HTFSI solution. (27th August 2022) - Chen, Wen; Chen, Jialiang; Deng, Junyi; Mo, Xiaolong; Yang, Wei; Zou, Hanbo; Chen, Shengzhou
Summary: A thin polyaniline layer that was covered on the surface of the microrod‐like lithium‐rich Mn‐based oxide (LMO, Li1.2 Mn0.54 Co0.13 Ni0.13 O2 ) was formed by in‐situ polymerization of the aniline monomer in HCl or (CF3 SO2 )2 NH (HTFSI) aqueous solution. The results of morphology analysis and structural characterization show that the uniform polyaniline coating layer has a thickness of 6 to 8 nm and the polymerization process does not spoil the integrity of the LMO microstructure. Electrochemical impedance spectroscopy and constant charge/discharge measurement show that polyaniline coating can significantly decrease the interfacial charge transfer resistance, and improve cyclic stability by reducing electrolyte corrosion. Cycling at the current density of 0.1 A g −1 for 100 cycles, the polyaniline‐coated LMO synthesized in HTFSI acidic media exhibits the discharge capacity of 212.2 mAh g −1 and high stability (91.98% retention of initial capacity). The high performance is a result of the activation of LMO in HTFSI acidic solution and the role of the (CF3 SO2 )2 N − counterions in the polyaniline chains. Abstract : Mechanism of polyaniline coating.